2006
DOI: 10.1007/s10546-006-9079-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation over a Heterogeneous Land Surface: EVA_GRIPS and the LITFASS-2003 Experiment—An Overview

Abstract: The Evaporation at Grid/Pixel Scale (EVA_GRIPS) project was realised in order to determine the area-averaged evaporation over a heterogeneous land surface at the scale of a grid box of a regional numerical weather prediction or climate model, and at the scale of a pixel of a satellite image. EVA_GRIPS combined surface-based and airborne measurements, satellite data analysis, and numerical modelling activities. A mesoscale field experiment, LITFASS-2003, was carried out in the heterogeneous landscape around the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 56 publications
1
66
0
Order By: Relevance
“…A total of 13 micrometeorological stations were deployed over this heterogeneous landscape to measure the turbulent fluxes of heat and momentum. More details about the experiment are found in Beyrich and Mengelkamp (2006).…”
Section: Eddy-covariance Measurementsmentioning
confidence: 99%
“…A total of 13 micrometeorological stations were deployed over this heterogeneous landscape to measure the turbulent fluxes of heat and momentum. More details about the experiment are found in Beyrich and Mengelkamp (2006).…”
Section: Eddy-covariance Measurementsmentioning
confidence: 99%
“…Patton et al (2005) showed that the strongest SCs occur if the ratio between the heterogeneity length scale and z i is between 4 and 9. Maronga and Raasch (2013), hereafter MR13, reported that the SCs contributed up to 20 % of the total sensible heat flux and up to 39 % of the total latent heat flux in their LES for the complex heterogeneous terrain of the LITFASS-2003 experiment (Beyrich and Mengelkamp 2006). In general, the existence of SCs throughout the bulk of the CBL conflicts with the concept of a blending height.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, soil water contents, soil temperatures and soil heat fluxes are measured operationally. For details of the investigation programme, instrumentation and measurement accuracy, the reader is referred to Beyrich et al (2002), , Beyrich and Mengelkamp (2006), Beyrich and Adam (2007) and Beyrich and Engelbart (2008). An overview of the measurements that were used in our study is given in Table 1.…”
Section: The Falkenberg Field Site and Micrometeorological Datamentioning
confidence: 99%